Faktor yang Berhubungan Dengan Stres Kerja Perawat Ruang Instalasi Gawat Darurat dan Ruang Intensive Care Unit - Ressy Herlia; Ririn Muthia Zukhra; Reni Zulfitri (STIKes Payung Negeri Pekanbaru, 2022)
One of the factors that affect the health of the workforce in employees can be in the form of physical and psychological disorders, including work stress caused by various factors including workload, work routine, bad organizational roles, economic problems, work environment. Every person who works will receive a load of what is done. The purpose of this research is to find out the factors related to the work stress of nurses in the emergency installation room and the intensive care unit. This research uses descriptive research with a cross sectional approach, the sampling method uses stratified random sampling technique, and uses a questionnaire instrument as a measuring tool. The sample of this study used 42 respondents consisting of 21 in the emergency room and 21 nurses intensive care unit room. Based on research in the emergency room, 14 respondents (66.7%) experienced heavy workload, 12 respondents (57.1%) watched work routines, 11 respondents (52.4%) had a bad organizational role. 13 respondents (61.9%) had a heavy workload, 10 respondents (47.6%) did not support the work environment, 10 respondents (47.6%) had family problems, 10 respondents (47.6%) had economic problems. 10 respondents (47.6%). It is hoped that hospital management can motivate nurses in the emergency room and intensive care unit to minimize stress.